ASSESSMENT AND INTERVENTION STRATEGIES FOR CHILDREN WITH HEARING IMPAIRMENTS IN SIDOARJO - Indrastata, Salsabila Noor; Rusyid Affandi, Ghozali (Antis-Publisher, 2025)
Objective: This study aims to explore the characteristics of children with hearing impairments and design suitable intervention strategies to support their development at UPTD Anak Berkebutuhan Khusus Sidoarjo. Method: A qualitative descriptive approach was used, employing observations and interviews, and guided by the TEACCH-based assessment matrix to analyze each child’s strengths and weaknesses. Results: The findings indicate notable strengths in sound detection, while significant challenges were observed in sound imitation and social interaction. Based on these assessments, individualized learning plans were formulated through collaborative efforts among teachers, parents, and therapists. A structured and consistent approach, including environmental support and periodic evaluations, was shown to enhance the child’s confidence and improve educational outcomes. Novelty: This study contributes to the limited research on region-specific interventions for children with hearing impairments in Indonesia, emphasizing the integration of TEACCH-based assessments within inclusive education frameworks. The collaborative model presented serves as a replicable approach for optimizing support systems and tailoring interventions to meet the evolving needs of children with special needs.